Exergy analysis of discharging multi-tank thermal energy storage systems with constant heat extraction. (15th September 2015) - Osorio, J.D.; Rivera-Alvarez, A.; Swain, M.; Ordonez, J.C.
Highlights: Dimensionless model for discharging multi-tank TES systems in series was developed. Uneven mass distribution provides higher efficiency for short discharging process. Variable mass distribution allows maximum efficiency during the entire time span. Optimum discharging times were determined for different operating conditions. Energy losses and pumping effects were analyzed. Abstract: In this work, an exergy analysis of discharging multi-tank thermal energy storage systems with constant heat extraction is studied. Theoretical models are developed to analyze the effect of the induced stratification through storage division into several tanks for different system configurations: multi-tank systems with even mass distribution, and two-tank systems with uneven and variable mass distribution. The instantaneous and the process efficiencies are defined to assess the performance of the system as function of operation parameters. For two- and four-tank systems with mass evenly distributed, efficiency increments around 4% and 7%, respectively, are possible. For two-tank systems, higher efficiencies are accomplished for short times when the mass is unevenly distributed and larger amount of the mass is in the hotter tank. For longer times, the even distributed mass situation provides the highest performance. To achieve superior efficiency of two-tank systems during the entire timespan, a time varying mass distribution χ = 0.5 ( 1 + e - 2 t ∗ ) is proposed. Finally, the energy losses as well as the pumping effects on the performance of one- and two-tank systems are analyzed. It is found that, both, the pumping effects and the energy losses are generally negligible and the efficiency can be improved dividing the storage system, rather than increasing the mass flow rate.